EFFECTIVE OR NOT: LEARNING ENGLISH THROUGH YOUTUBE - Ghifari Mabrur Al Burhani; Aniza Mar’atus Sholekhah; Fatikha Ilma Nuril Khusna (2025)
This study examines YouTube’s effectiveness as a tool for English language learning, focusing on its influence on language acquisition, student perceptions, content preferences, and educational integration. Using a descriptive quantitative approach, data were collected through a survey questionnaire comprising 14 closed-ended and one open-ended question targeting English student college. The results show that YouTube improves vocabulary, grammar, pronunciation, and listening comprehension. BBC Learning English, English with Lucy, and Lingua Marina are well-known organized channels. Distractions, false information, and a lack of organized direction were noted as problems, nevertheless. To maximize YouTube's extensive resources, the study emphasizes the value of integrating it into formal education through carefully selected playlists and self-regulated learning techniques. Teachers can provide students with freedom and crucial feedback by integrating YouTube with conventional classroom techniques, resulting in a well-rounded learning strategy. Diverse learning styles were shown by open-ended responses, with some students using unconventional content, such as social media and video games to increase their vocabulary. According to the study's results, carefully incorporating YouTube into curricula can greatly improve students' English language proficiency. Future research should look at how different YouTube videos affect particular linguistic abilities and how student engagement is affected by tailored algorithms.